1998
DOI: 10.1080/01140671.1998.9514058
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between canopy density and fruit quality of kiwifruit

Abstract: The influence of canopy density on fruit quality was investigated during 2 years in two commercial kiwifruit (Actinidia deliciosa 'Hayward') orchards in Te Puke, New Zealand. One orchard had a history of producing fruit which store well, whereas the other tended to have a dense canopy, and high losses of fruit during coolstorage. In each orchard we adjusted pruning regimes to produce open, or dense canopies, with mean leaf area index (LAI) values ranging from 3.0 to 5.5. There was a tendency for vines with den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…The anti‐oxidant potential of Actinidia fruits was found to be largely influenced by vitamin C and total polyphenol levels, but also dependent on species and cultivars (Du et al ., ). The kiwifruit quality depends on several factors such as ripening time, genotype, cultivation techniques and environmental conditions (Kempler et al ., ; Snelgar et al ., ; Ferguson, ). The polyphenol content of kiwifruits was also influenced by light exposure, harvest time and storage conditions during the post‐harvest (Montanaro et al ., ; Tavarini et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…The anti‐oxidant potential of Actinidia fruits was found to be largely influenced by vitamin C and total polyphenol levels, but also dependent on species and cultivars (Du et al ., ). The kiwifruit quality depends on several factors such as ripening time, genotype, cultivation techniques and environmental conditions (Kempler et al ., ; Snelgar et al ., ; Ferguson, ). The polyphenol content of kiwifruits was also influenced by light exposure, harvest time and storage conditions during the post‐harvest (Montanaro et al ., ; Tavarini et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Areas of dense canopy and high crop load near the trunk of vines may result in poor quality fruit. Studies of'Hayward' kiwifruit vines have shown that shading adversely affects both fruit size and quality (Grant & Ryugo 1984;Snelgar et al 1992Snelgar et al , 1998. If this is also true of A. chinensis cultivars, pruning techniques may have to be modified to reduce the number of canes in this region, thereby reducing canopy density and crop load.…”
Section: Vine Managementmentioning
confidence: 99%
“…In a study on the effect of canopy density on fruit quality the relationships between leaf area index and fruit size in Hayward cultivar was investigated. The results showed that the fruit size decreased as the crop load increased at a rate of 0.2 g/fruit/m 2 (SNELGAR et al , 1998. COOPER and MARSHALL (1992) also reported that leaf number/fruit ratio had a greater effect on fruit size than the crop load, and that the greatest fruit size and extra yield were obtained with 3:1 ratio.…”
mentioning
confidence: 92%